2016
DOI: 10.1177/1071100716628912
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Malunion Following Bi-plane Chevron Medial Malleolar Osteotomy

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 18 publications
1
33
0
1
Order By: Relevance
“…In our series, no cases had an uneven articular surface of the tibial plafond at the malleolar osteotomy site visually, and the measured results were much lower than those reported by Bull and colleagues. 3 Also, all ankles in the current study achieved union at 7.3 ± 1.5 weeks, which is similar to the union time of chevron-type medial malleolar osteotomy. 13 The type of fixation plays an important role in the prevention of osteotomy displacement.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our series, no cases had an uneven articular surface of the tibial plafond at the malleolar osteotomy site visually, and the measured results were much lower than those reported by Bull and colleagues. 3 Also, all ankles in the current study achieved union at 7.3 ± 1.5 weeks, which is similar to the union time of chevron-type medial malleolar osteotomy. 13 The type of fixation plays an important role in the prevention of osteotomy displacement.…”
Section: Discussionsupporting
confidence: 81%
“…The more recent biplane chevron and step-cut osteotomy techniques provide wider exposure, a broad cancellous surface for healing, and greater intrinsic theoretical stability. 9 , 18 However, Bull et al 3 showed that biplane chevron medial malleolar osteotomy fixed with 2 lag screws had a 30% malunion rate, with an average of 2 mm of incongruence on final follow-up radiographs. Displacement after osteotomy can lead to advanced ankle osteoarthritis.…”
mentioning
confidence: 99%
“…Ein wesentlicher Nachteil ist, dass trotz aller Maßnahmen, wie Vorbohren der Schraubenlöcher für die spätere Ostsynthese vor der eigentlichen Osteotomie, Einsatz einer zusätz-lichen Schraube parallel zum Gelenksspalt, Durchtrennen des Knochens mit dem Meißel oder auch einer domför-migen Osteotomie, häufig kleine Stufen verbleiben, die als Risikofaktor für eine spätere Arthroseentwicklung angesehen werden. Dies wird umso deutlicher, je häufiger Schnittbildverfahren im weiteren Krankheitsverlauf angefertigt werden [5,18].…”
Section: Operativer Zugang Mit Innenknöchelosteotomieunclassified
“…In a study of 50 biplane medial malleolar osteotomies, 30.0% of cases had a malunion with a mean incongruency of 2 mm. 4 However, for fixation of OLT, unlike the exposure required for autologous osteochondral transplantation and allografting, the entire lesion does not have to be exposed and malleolar osteotomy is not always required. In a cadaveric study, 33% of the talus in the anteroposterior length and 30% of its mediolateral length could be reached by posteromedial arthrotomy without malleolar osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…11,33 Even for adults, malleolar osteotomy entails some complications. 4 However, unlike the exposure required for autologous osteochondral transplantation and allografting for the placement of large osteochondral plugs or an allograft block, for fragment fixation, the entire lesion does not have to be exposed and a malleolar osteotomy is not always required. We developed a method to approach the lesion without malleolar osteotomy.…”
mentioning
confidence: 99%